Electrochemical and Spectroscopic Studies on the Interaction Between DNA and Chromotrope 2B - Niu, S.Y.; Zhang, S.S.; Xu, H.; Jiao, K. (Asian Journal of Chemistry, 2016)
Differential pulse voltammetry was used to study the interaction of salmon sperm DNA with chromotrope 2B (CT2B). CT2B had irreversible oxidation peaks in 0.2 mol L-1 Britton-Robinson (B-R) buffer solution at pH 5.0 on a glassy carbon electrode. After adding certain concentration of DNA, the oxidation peak current of CT2B decreased and the peak potential positively shifted. It was further investigated by UV/Vis spectroscopy and fluorescence spectroscopy. The hypochromic effect of the absorption peak and phenomena of bathochromic effect appeared. In addition, the increases of fluorescence were observed after CT2B was added to DNA. Quenching fluorescence phenomenon was observed in EB-DNA system when CT2B was added. All the experimental results showed that the binding mode of CT2B with DNA was intercalative binding. The binding ratio of the DNA-CT2B association complex was calculated to be 1 : 2 and the binding constant was 2.57 × 105 L2 mol-2.